Adolescents' reproductive health knowledge, choices and factors affecting reproductive health choices: a qualitative study in the West Gonja District in Northern region, Ghana - Joseph Maaminu Kyilleh; Philip Teg-Nefaah Tabong; Benson Boinkum Konlaan (BMC, 2018)
Abstract Background In Ghana, adolescents constitute about a quarter of the total population. These adolescents make reproductive health decisions and choices based on their knowledge and the availability of such choices. These reproductive health decisions and choices can either negatively or positively affect their lives. This study therefore explored adolescents' reproductive health knowledge and choices, the type of choices they make and the factors that affect these choices. Methods This qualitative study adopted a narrative approach to qualitative enquiry. Eight focus group discussions (N = 80) were conducted among both in-school and out-of-school adolescents aged 10-19 years. The discussions were stratified by sex and studentship. In addition, nine in-depth interviews were conducted with various stakeholders in reproductive health services and community opinion leaders. Both the focus group discussions and in-depth interviews were recorded, transcribed and analysed using NVivo 11. Thematic analysis was employed in analysing data. Results The study found that knowledge on reproductive health choices was low among respondents with majority of them relying on their peers for information on sexual and reproductive health. Having a sexual partner(s) and engaging in premarital sex was common and viewed as normal. Adolescents engaged in unprotected sexual practices as a way of testing their fertility, assurance of love, bait for marriage and for livelihood. Inserting herbs into the vagina, drinking concoctions and boiled pawpaw leaves were identified as local methods employed by adolescents to induce abortion. Reproductive health services were available in the community but received low utilization because of perceived negative attitude of health workers, confidentiality and social norms. Conclusions Adolescents in this study generally engaged in risky reproductive health choices that can negatively affect their reproductive health. Adolescents in this part of Ghana have challenges utilizing available reproductive health services because of socio-cultural and health system barriers.